Implementasi API pada Aplikasi Al-Qur'an Berbasis Android dengan Metode UCD - Ira Purnama Sari; Iwan Purnama; Ali Akbar Ritonga (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Al-Qur'an is a source and argument for Islamic law, kalam experts, science experts and not only books that speak Arabic and read worship, but also contain scientific value and become a life guide for the development of human cultural reason. especially Muslims. The purpose of this research is to implement the API in the Al-Quran application based on Android and the method used by UCD (User Centered Design). An API is a set of program instructions that are used to build a software application, by providing functions and commands in a language that is easy for the programmer to understand. UCD (User Centered Design) is a design philosophy that places the user at the center of a systems development process. The results showed that an Android-based Al-Qur'an application was in accordance with the needs of the user and the average test results shared with users was 81.25%